Tiny thoughts on patience - Bezenac, Agnes; Bezenac, Salem (Beirut Dar al Maaref bookshop, 2020)
Patience is usually the best way, things don't always work out the way we hope they will when we get impatient
Education
1
Keywords: Educational psychology